Artificial regeneration with Quercus ilex L. and Quercus suber L. by direct seeding and planting in southern Spain - González-Rodríguez, Victoria; Navarro-Cerrillo, Rafael M.; Villar, Rafael (Annals of Forest Science, 2011)
& Introduction The limited ability of Quercus species to regenerate naturally in Mediterranean forests has led to the development of various artificial regeneration methods; however, there is no general consensus as to what specific method is the best one for this purpose. & Material and methods In this work, we assessed morphology, growth and survival of two Quercus species (Quercus ilex ssp. ballota and Quercus suber) using two different methods of artificial regeneration (viz. direct seeding and planting) and two seedling ages (1-year-old seedlings and 3-year-old seedlings) in southern Spain. & Results and discussion The 1-year-old seedlings of both species were found to exhibit the highest survival percentages and direct-seeded plants intermediate survival values. For direct-seeded plants, seed mass was found to have a significantly positive effect on the establishment success in both species. No clear-cut trend in survival was detected in the 3- year-old seedlings. The survival of the 3-year-old Q. suber seedlings and the direct-seeded plants was similar, but not in Q. ilex, where the survival of the 3-year-old seedlings was the lowest. The latter result may have been a consequence of cultivation in smaller containers leading to root deformation and limiting plant access to water. Differences in survival could not be ascribed to morphological and growth variables or stomatal conductance. & Conclusion Based on the results, all three artificial regeneration methods can be similarly effective provided appropriate nursery cultivation conditions are used and seeds are protected against predators, the best choice in each case being dictated by the particular restoration goals.
Keywords: artificial regeneration; Nursery; oak; Seedling; sowing

Repoblación con semillas o plántulas: un experimento con encina y alcornoque - González-Rodríguez, Victoria; Villar, Rafael; NAVARRO- CERRILLO, RAFAEL (V Congreso Forestal Español, 2009)
El éxito de una repoblación forestal depende de muchos factores como son las condiciones ambientales del lugar de establecimiento, la calidad de la plantación y la evolución posterior de los factores ambientales. Aunque actualmente el método de repoblación más frecuente es la plantación con planta de vivero, todavía existe controversia sobre si esta opción es más adecuada que la siembra, en particular para especies del genero Quercus. Por otro lado, en el caso de utilizar brinzales, pueden existir diferencias en el establecimiento en función de su edad y de las características morfológicas iniciales. En este trabajo se compara la supervivencia y el crecimiento de plántulas de Quercus ilex y Q. suber según el método de repoblación (siembra o plantación) y la edad de la planta de vivero (1 y 3 savias). La supervivencia al final del primer año no mostró diferencias significativas entre tratamientos para Quercus suber, pero en Q. ilex se obtuvo una mayor supervivencia en plántulas de una savia y en la siembra que en plántulas de tres savias. Las plantas más jóvenes presentaron mayor inversión en hojas y menores en tallo y raíces que las plantas de 3 años
Keywords: bellota; crecimiento; Q. ilex; Q. suber; restauración; supervivencia